2010
DOI: 10.1038/modpathol.2009.167
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of Ki67 is dependent on estrogen receptor status and histological grade in premenopausal patients with node-negative breast cancer

Abstract: The aim of this study was to evaluate the prognostic value of Ki67 in relation to established prognostic factors in lymph node-negative breast cancer, and furthermore, whether the prognostic impact was dependent on estrogen receptor (ER) status and histological grade. In 200 premenopausal patients, with 5 years of follow-up, Ki67 was determined on tissue microarrays. In univariate analysis, Ki67 (r20 vs 420%) was a prognostic factor for distant disease-free survival (hazard ratio: 2.7, 95% confidence interval:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
69
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 32 publications
9
69
1
2
Order By: Relevance
“…In line with this, a recent study from our group has shown that the proliferation marker Ki67 was of prognostic importance only in ER-positive breast cancers [18]. In that study, we also showed that the prognostic importance of Ki67 was dependent on histological grade [18], again showing similarities with gene expression data [14,15]. The latter finding was recently confirmed in a consecutive series consisting of more than 1,500 patients [19].…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…In line with this, a recent study from our group has shown that the proliferation marker Ki67 was of prognostic importance only in ER-positive breast cancers [18]. In that study, we also showed that the prognostic importance of Ki67 was dependent on histological grade [18], again showing similarities with gene expression data [14,15]. The latter finding was recently confirmed in a consecutive series consisting of more than 1,500 patients [19].…”
Section: Introductionsupporting
confidence: 76%
“…In the ER-positive subgroup, genes associated with proliferation seem to be the most important, whereas genes associated with immune response are more important among ER-negative breast cancers [16,17]. In line with this, a recent study from our group has shown that the proliferation marker Ki67 was of prognostic importance only in ER-positive breast cancers [18]. In that study, we also showed that the prognostic importance of Ki67 was dependent on histological grade [18], again showing similarities with gene expression data [14,15].…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Ki67 has the correlation with differentiation degree, tumor invasion, metastasis and prognosis of many tumors. The patients with ki67 positive expression have poor prognosis (Klintman et al, 2010). In this study, although the absolute value of expression intensity and positive rate of Ki67 in PTMC was not very high, the expression intensity was below 25%, but it had statistical significance with the differences between PTMC and benign lesions with papillary hyperplasia.…”
Section: Discussionmentioning
confidence: 82%
“…3,6,17 A threshold proportion of Ki67 positivity within the range of 20 to 29% to distinguish the highly proliferative 'Luminal B-like' disease from the lowly proliferative 'Luminal A-like' disease is however mentioned, 5 and at our and several other institutions a cutoff of ≥ 20% for highly proliferative tumors is commonly used. 4,[18][19][20][21] The most recent version of these guidelines mentions that this uncertainty and variability may be reduced by image analysis, but provides no further details on how to apply this to biomarker testing in practice. 5 Hence, in this study we aim to contribute with precisely that; we take an equally broad and detailed approach on manual and digital image analysis (DIA) evaluation of biomarkers in invasive breast cancer by comparing a novel system of DIA with the manual immunohistochemical method used in current clinicopathological routine for performance in subclassification and prognostication.…”
mentioning
confidence: 99%